Extracting performance data from great piano performances - extraction of performance data - Chua, Chanel Wan Ting (2018)
Audio recordings provide mankind with a form of historical preservation. They provide us with an opportunity to have a glimpse into the past on what life was like during that era. Since the mid-19th century, music were recorded in the form of analog signals and stored either in tapes or records. Not only that, excessive mechanical tension can degrade tapes and records. For example, each time a cassette is being loaded into a recorder, the mechanism may damage the tape if the guide pins are not properly aligned. When a tape is being ejected from the recorder, it must also be ejected properly to avoid damaging the tape. At tape running through a cleaning machine under certain conditions can also stretch the tape and introduce skew error. Finally, weather conditions can also cause the cassette tape to degrade. During production, the substrates are pre-stretched and if the tapes are being heated up again, they may deform. Excessive climate fluctuations may also cause the tape to shrink. No matter how the tapes or records are treated by the user, degradation can only be controlled to a certain extent, as they have a limited shelf life. Fortunately, with the level of technology we have today, we are able preserve our music through digitization. This ensures that we would have a digital copy of the audio even if the physical media is no longer playable.